BALANCE POSTURAL ASSESSMENTS AND FUNCTIONAL MOBILITY IN SUBJECTS WITH KNEE OSTEOARTHRITIS - Moreira, Ana Carolina Silva De Souza; Santos, Gilmar Moraes (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
INTRODUCTION: Knee Osteoarthritis (KOA) affects joint cartilage causing pain, musculoskeletal and proprioceptive disorder that may favor the occurrence of postural balance disorders during activities of daily living. OBJECTIVE: To analyze the clinical variables, the balance profile and the functional mobility of subjects with KOA with and without a history of falls. METHODS: Sixty-four women, 50 to 75 years of age, were separated into three different groups: KOAF group (18 subjects with KOA and previous history of falls); KOANF (24 subjects with KOA and no previous history of falls) and control group - CG (22 healthy subjects). The Womac questionnaire was used to analyze functional disability. For the functional evaluation of the balance, two instruments were used, the Berg’s Balance Scale (BBS) and the Timed Up and Go test (TUG). For static balance evaluation, was used the stabilization diffusion analysis method (SDA) and analysis of the balance stabilizer of center of pressure (COP). RESULTS: It was evidenced that the BBS and WOMAC scores were significantly lower for the KOA group. The functional evaluation of the balance showed that the TUG test time and BBS score were significantly lower in subjects with KOA than in CG. The KOA groups (KOAF and KOANF) presented a greater displacement of the COP, anterior-posterior (AP) direction, and ellipse area than CG, in the closed-eyes condition. The KOAF group showed higher average speed of COP than CG. In the analysis of stabilogram diffusion, for both visual conditions, the KOA groups presented higher values in the short-term interval, long-term interval and critical point position than CG in the AP direction. CONCLUSION: The results imply that subjects with KOA, regardless of the previous history of falls, show a deficit of balance, increasing the risk of falls in this population.